Characteristics of Organic and Inorganic Substances in Leachate Wastewater Talumelito Regional Waste Final Disposal Site - Zikran Abdullah; Sahrial Lakasim; Siti Hairunisa Kandusu; Mahdi Kilo; Wiwin Rewini Kunusa (Jambura Journal of Chemistry, 2022)
Leachate or leachate is a solution that occurs as a result of mixing rain runoff with decomposed trash and containing very fine suspended substances and pathogenic microbes that can cause potential contamination of surface water and groundwater. This study aims to analyze organic and inorganic substances (Pb, Cd, Mn, Fe and Cu metals) in leachate waste. Leachate water sampling was carried out at the Talumelito Waste Disposal Site, Gorontalo District by composite sampling at 5 location points, namely A1, A2, A3, A4, A5. The research procedure was divided into 4 stages, namely the preparation phase, the sampling stage, the sample analysis stage and the data analysis stage. Metal analysis using the AAS method. The results of the analysis at 5 location points showed the highest Lead (Pb) metal reached 0.0248 ppm, Cadmium (Cd) ˂ 0.0009 ppm and Copper (Cu) ± 0.02 ppm. For iron (Fe) the highest reaches 3.1029. For Manganese metal (Mn), they are 1.2779 ppm, 1.1441 ppm and 1.2779 ppm. Heavy metal parameter, the value is still far below the quality standard for leachate in samples A1, A2, A3, A4, and A5. As for the analysis of organic substances, nitrates and nitrites using the Uv-Vis spectrophotometry method showed the highest levels of organic matter were 40.97, nitrates 5.77 and nitrites 0.0065. However, the pH value is above the leachate quality standard of 6.9 at 3 location points, 7.8 - 8.2. And turbidity level of leachate for sample A1 reaches 135.5. From these results it can be seen that the function of the leachate control pool in the Talumelito landfill is still ineffective.